Integration of Photosensors in a Nano-liter Scale Chromatography Column for the Online Monitoring of Adsorption/Desorption Kinetics of a Fluorophore-labeled Monoclonal Antibody. (2016) - Pinto, Inês F.; Santos, D.R.; Soares, R.R.G.; Aires-Barros, M.R.; Chu, V.; Azevedo, A.M.; Conde, J.P.
Abstract: Chromatography is a robust purification technique, but requires time-consuming optimization on a case-by-case basis, particularly for monoclonal antibodies (mAbs). This work presents a novel microfluidic platform that significantly speeds up the optimization process and reduces the amount of reagent needed. Binding kinetics for a fluorescent conjugate mAb-Alexa 430 were measured in real time at resin level by integration of the microfluidic chip with 200×200 μm a-Si:H photodiodes on glass substrates aligned with micro-columns. Screening studies were performed using reduced amounts of reagents (∼50 μL), mAb molecules (∼2.5 μL) and resin (∼70 nL) in a rapid (∼2 min/condition) and simple manner.